1989
DOI: 10.1073/pnas.86.13.5015
|View full text |Cite
|
Sign up to set email alerts
|

Plant retrotransposon from Lilium henryi is related to Ty3 of yeast and the gypsy group of Drosophila.

Abstract: The lily retrotransposon del 146 is 9345 base pairs (bp) long. It has long terminal repeats (LTRs) of 2406 bp (left) and 2415 bp (right), which differ in sequence by 1.4%. Sequences similar to those involved in priming DNA synthesis in retroviruses occur in the internal region. Near the left LTR is a sequence complementary to 18 residues at the 3' end of methionine initiator tRNA of three plant species, and a run of 12 purines occurs close to the right LTR. One internal reading frame of del 1-46 has relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
83
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 40 publications
1
83
0
Order By: Relevance
“…Two classes of retrotransposons have been identified: the long terminal repeat (LTR) retrotransposons (flanked by LTRs) and the non-LTR retrotransposons. Regarding their sequence homology and gene organization, two major groups of LTR retroelements, the Ty1/copia and the Ty3/gypsy, have been distinguished (Grandbastien, 1992); representatives of both groups have been found in higher plants Smyth et al, 1989;Flavell et al, 1992;Voytas et al, 1992).…”
mentioning
confidence: 99%
“…Two classes of retrotransposons have been identified: the long terminal repeat (LTR) retrotransposons (flanked by LTRs) and the non-LTR retrotransposons. Regarding their sequence homology and gene organization, two major groups of LTR retroelements, the Ty1/copia and the Ty3/gypsy, have been distinguished (Grandbastien, 1992); representatives of both groups have been found in higher plants Smyth et al, 1989;Flavell et al, 1992;Voytas et al, 1992).…”
mentioning
confidence: 99%
“…Recent studies have indicated that the majority of this reiterated DNA is composed of retroelements, severa1 classes of mobile DNA that transpose through an RNA intermediate (Smyth et al, 1989;Moore et al, 1991;Pearce et al, 1996;SanMiguel et al, 1996;Suoniemi et al, 1996). In maize, a particular class of retroelements with long-terminal repeats (LTRs), the retrovirus-like retrotransposons, is most abundant.…”
mentioning
confidence: 99%
“…The internal domain contains a single 3927-bp open reading frame (QRF), and the predicted 1309 amino acid sequence includes both the gag and pol regions. A single ORF including both the gag and pol genes is unusual but is known in the Tf elements (5), in copia and its close relatives (19), and in micropia (26 4 (4,9,15). A short region of the presumptive protease gene is shown in Fig.…”
mentioning
confidence: 99%
“…Immediately interior to the 5' LTR is a putative tR14A primer binding site for (-)-strand synthesis that begins with the, sequence TGG. Sea urchin nuclear tRNAs have not been characterized; however, starting with the TGG sequence, SURL1-3 (Tg) shares 11 of 12 bases with the methionine tRNA primer binding site of both RL elements Tal-3 ofArabidopsis (10) and del of lily (9). Tyl (3) and Ty3 (4) of yeast are also both inferred to be primed with methionine tRNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation